Antiphospholipid antibodies in forty young patients with stroke - AL- Khalissi, Khudhair A.; Abass, Mohamed S.; Nabat, Ali A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Cerebral ischemia associated with Antiphospholipid Syndrome(APS) is a common arterial manifestation in adults.Objectives: To look for the frequency of Antiphospholipid Antibodies (aPL), and their relation with other risk factors in young patients with cerebral ischemia.Patients and methods: A retrospective study of 40 young patient’s ≤ 50 years with stroke collected from medical and neurological wards of Baghdad Teaching Hospital (BTH) from January - December 2009. All were inquired about the presence of risk factors of stroke, and sent for aPL including Anticardiolipin (ACL) and Lupus Anticoagulant (LA).Results: Eight (20%) had ACL. Nine (22.5%) had LA. Both were present in 6(15%). ACL and/or LA were present in 11 (27.5%). Thirty three (82.5) patients had at least one risk factor, 8 of them had aPL, while 7(17.5%) had no risk factor and only 3 of them had aPL (p 0.1806).Conclusion: Antiphospholipid Syndrome is a possible risk factor of stroke and any young patient with stroke should be screened for aPL .